Young Adults NEET and Everyday Life: Time Management and Temporal Subjectivities. (February 2019) - Gaspani, Fabio
The article investigates the everyday realities of young adults who are not in education, employment or training (NEET) in Italy and focuses on both time management and temporal subjectivities. In reference to the first point, the analysis of individuals' typical days reveals different temporal organization strategies and the activities they consider important to structure their time. As for the study of temporal subjectivities, the article deals with the representations and control on everyday time, which are determined not only by the amount of time spent for specific activities but also by how such activities are performed, taking into account the interactions with others and the contexts. The study of NEET experiences allow a reflection both in reference to youth difficulties in managing time and their agency in an age of uncertainty.